Bryophyte Conservation in Managed Boreal Landscapes: Fourteen-Year Impacts of Partial Cuts on Epixylic Bryophytes - Opoku-Nyame, Jeffrey; Leduc, Alain; Fenton, Nicole J. (Frontiers in Forests and Global Change, 2021)
Clear cut harvest simplifies and eliminates old growth forest structure, negatively impacting biodiversity. Partial cut harvest has been hypothesized 1) to have less impact on biodiversity than clear cut harvest, and 2) to encourage old growth forest structures. Long-term studies are required to test this hypothesis as most studies are conducted soon after harvest. Using epixylic bryophytes as indicators, this study addresses this knowledge gap. Fourteen years after harvest, we examined changes in epixylic bryophyte community composition and richness, and their microhabitats (coarse woody debris characteristics and microclimate) along a harvest gradient (unharvested, partial cuts and clear cuts) in 30 permanent plots established in the boreal black spruce forests of northwestern Quebec, Canada. Our results were compared to those of an initial post-harvest study (year 5) and to a chronosequence of old growth forests to examine species changes over time and the similarity of bryophyte communities in partial cut and old growth forests. Coarse woody debris (CWD) volume by decay class varied among harvest treatments with partial cuts and clear cuts recording lower volumes of early decay CWD. The epixylic community was richer in partial cuts than in mature unharvested forests and clear cuts. In addition, species richness and frequency of occurrence doubled in partial and clear cuts between year 5 and 14. Lastly, over time, species composition in partial cuts became more similar to old growth forests. Partial cuts reduced harvest impacts by continuing to provide favorable microhabitat conditions that support epixylic bryophytes. Also, partial cut harvest has the potential to encourage old growth species assemblages, which has been a major concern for biodiversity conservation in managed forest landscapes. Our findings support the promotion of partial cut harvest as an effective strategy to achieve species and habitat conservation goals.